Field evaluation of Bt 127 SC formulation against Spodoptera litura (F.) in soybean: Field evaluation of Bt 127 SC formulation against Spodoptera litura (F.) in soybean - R CHANNAKESHAVA; SANGSHETTY; G SOMANAGOUDA; SHALINI N HUILGOL; G T BASAVARAJA; C J KUMAR (Journal of Oilseeds Research, 2020)
Bt 127 SC formulation was field tested against Spodoptera litura larvae infesting soybean at Dharwad. Among the biopesticides, Bt 127 SC formulation @ 3 ml/l of water has proved to be significantly superior over commercial Bt formulation Delfin and untreated control and recorded lowest S. litura after both the sprays. There was a higher reduction in larval population on the seventh day after treatment both in Bt 127 SC formulation (0.54 l/mrl) and Bt commercial Delfin (0.75 l/mrl) treated plots as bacterial infection starts to manifest leading to high mortality of larva within 3-5 days after treatment. Soybean seed yield due to treatment by Bt 127 SC formulation (1733 kg/ha) and Bt commercial Delfin (1694 kg/ha) were on par but lower in comparison to the broad spectrum chemical insecticides that are effective against different orders of insects. There was negligible population of natural enemies in the plots before and after the treatments.